2014
DOI: 10.3171/2014.7.spine13965
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography–guided epidural patching of postoperative cerebrospinal fluid leaks

Abstract: Object Cerebrospinal fluid leaks due to unrecognized durotomy during spinal surgery are often managed with a second surgery for dural closure. CT-guided percutaneous patching targeted to the dural defect offers an alternative to surgery since it can be performed in a minimally invasive fashion without the need for general anesthesia. This case series describes the authors' experience using targeted CT-guided percutaneous patching to repair incidental durotomies incur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 7 publications
2
15
0
2
Order By: Relevance
“…Several methods are used for the management of CSF leak including direct suturing 1,6) , percutaneous injection 7,8) , drainage therapy [9][10][11] , and blood patch 9,[12][13][14] . One well-known and widely accepted management option is surgical repair by either meticulous direct primary closure of the dura or augmented closure by means of fat, muscle tissue, or a fascia graft.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods are used for the management of CSF leak including direct suturing 1,6) , percutaneous injection 7,8) , drainage therapy [9][10][11] , and blood patch 9,[12][13][14] . One well-known and widely accepted management option is surgical repair by either meticulous direct primary closure of the dura or augmented closure by means of fat, muscle tissue, or a fascia graft.…”
Section: Discussionmentioning
confidence: 99%
“…evaluated the efficacy of repairing postoperative CSF fistulas utilizing MI, percutaneous CT-guided epidural patching. [ 12 ] The study retrospectively identified 9 such cases utilizing CT myelography; those effectively treated percutaneously had dural defects of 4 mm or less without pseudomeningoceles, while those with larger defects and pseudomeningocele could not be managed with this percutaneous strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Bei Leckagen bis zu einer maximalen Grö-ße von 5 mm ist der "blood patch" meist erfolgreich, bei größeren Leckagen kann eine offene operative Versorgung erforderlich werden [14]. Sollte der "blood patch" bei kleineren Leckagen auch nach der dritten Anwendung noch nicht suffizient sein, besteht als weitere Therapieoption die CTAbb.…”
Section: "Blood Patch"unclassified
“…Der erste "blood patch" ist in bis zu 85% der Fälle wirksam, nach einmaliger Wiederholung wird bereits eine Wirksamkeitsrate von bis zu 98% erreicht [1,2,4,5,9,12,14,18,21,23,28]. Da manche Patienten mit spontanem Liquorverlustsyndrom auf mehreren Höhen Liquorlecks aufweisen, können mehrere "blood patches" auf verschiedenen Höhen erforderlich sein.…”
Section: Ergebnisseunclassified